2021
DOI: 10.1007/s12672-021-00435-4
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of the HECT-type E3 ubiquitin ligases in hematological malignancies

Abstract: Ubiquitination-mediated proteolysis or regulation of proteins, ultimately executed by E3 ubiquitin ligases, control a wide array of cellular processes, including transcription, cell cycle, autophagy and apoptotic cell death. HECT-type E3 ubiquitin ligases can be distinguished from other subfamilies of E3 ubiquitin ligases because they have a C-terminal HECT domain that directly catalyzes the covalent attachment of ubiquitin to their substrate proteins. Deregulation of HECT-type E3-mediated ubiquitination plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 119 publications
(148 reference statements)
0
1
0
Order By: Relevance
“…In our study, the GSEA analysis showed that ubiquitin-mediated proteolysis and purine metabolism were active in the high-risk group, and fat metabolism was active in the low-risk group. Ubiquitin-mediated proteolysis carried out by the action of E3 ubiquitin ligases, regulates a series of cellular processes, including gene transcription, cell autophagy and apoptosis [37] . In another study, the authors proposed that targeted inhibition of purine metabolism can effectively inhibit HCC progression [38] .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the GSEA analysis showed that ubiquitin-mediated proteolysis and purine metabolism were active in the high-risk group, and fat metabolism was active in the low-risk group. Ubiquitin-mediated proteolysis carried out by the action of E3 ubiquitin ligases, regulates a series of cellular processes, including gene transcription, cell autophagy and apoptosis [37] . In another study, the authors proposed that targeted inhibition of purine metabolism can effectively inhibit HCC progression [38] .…”
Section: Discussionmentioning
confidence: 99%